2016
DOI: 10.1088/0964-1726/25/11/115038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a negative Poisson’s ratio on thermal stresses in cellular metallic structures

Abstract: To investigate the influence of auxetic behavior on thermally induced stresses, finite element analysis  simulations of the displacement and stress fields in locally heated three dimensional auxetic and cubic structures are compared. The simulations were carried out in Comsol for a cubic as well as a chiral array of 30 mm length in each spatial dimension (3 × 3 × 3 unit cells). The center cells of these arrays were heated for 20 s. For two boundary conditions (free and clamped), deformation mechanisms are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The selective electron beam melting (SEBM) process enables the production of very complex parts, such as cellular metals [ 39 ]. It has been shown that the process is suited to fabricate cellular auxetic structures with the ability to control relative density [ 40 , 41 , 42 , 43 ]. Furthermore, phononic band gap structures were produced by SEBM and the existence of the complete PBGs was already experimentally verified [ 21 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selective electron beam melting (SEBM) process enables the production of very complex parts, such as cellular metals [ 39 ]. It has been shown that the process is suited to fabricate cellular auxetic structures with the ability to control relative density [ 40 , 41 , 42 , 43 ]. Furthermore, phononic band gap structures were produced by SEBM and the existence of the complete PBGs was already experimentally verified [ 21 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The model was built using solid elements (ABAQUS element type C3D8R with a mesh sweeping seed size of 0.2-0.3 mm, as shown in Figure 18(d) and (e)). The seed size was selected by the criterion of a maximum deviation of 3% of the maximum von Mises stress when the element size was halved (Adler et al, 2016). The material properties used in the simulation come from tensile test results of SMA wires.…”
Section: Feamentioning
confidence: 99%